Planning for HIV preexposure prophylaxis introduction: lessons learned from contraception. Issue 1 (January 2016) - Delany-Moretlwe, Sinéad; Mullick, Saiqa; Eakle, Robyn; Rees, Helen
Abstract : Purpose of review: We summarize key lessons learned from contraceptive development and introduction, and implications for preexposure prophylaxis (PrEP). Recent findings: New approaches to HIV prevention are urgently needed. PrEP is a new technology for HIV prevention. Uncertainty remains about its acceptance, use and potential to have an impact on the HIV epidemic. Despite imperfect use and implementation of programs, the use of modern contraception has led to significant reproductive health and social gains, making it one of the public health's major achievements. Guided by the WHO strategic approach to contraception introduction, we identified the following lessons for PrEP introduction from contraception: (1) the importance of a broader focus on the method mix rather than promotion of a single technology, (2) new technologies alone do not increase choice – service delivery systems and providers are equally important to success, and (3) that failure to account for user preferences and social context can undermine the potential of new methods to provide benefit. Summary: Taking a strategic approach to PrEP introduction that includes a broader focus on the technology/user interface, the method mix, delivery strategies, and the context in which methods are introduced will benefit HIV prevention programs, and will ensure greater success.